Defining Off-road Running: A Position Statement from the Ultra Sports Science Foundation - Scheer, Volker; Basset, Patrick; Giovanelli, Nicola; Vernillo, Gianluca; Millet, Gregoire P.; Costa, Ricardo J. S. (International Journal of Sports Medicine, 2020)
Off-road running continues to grow in popularity, with differing event categories existing, and terminologies are often used interchangeably and without precision. Trail running, mountain running, skyrunning, fell running, orienteering, obstacle course racing and cross-country running all take place predominantly in off-road terrain. Ultramarathon running refers to any running event over marathon distance conducted in any terrain and surface. Although some overlap may exist between these running events, mainly through the common denominator of off-road terrain, distinct features need to be recognised. As scientific interest in these activities grows, it becomes important to clarify these terms and develop a universal language for discussing these events. Similarly, off-road running athletes are generally not properly defined within the scientific literature, which makes intra- and inter-study comparisons difficult. The current position statement of the Ultra Sports Science Foundation highlights the different off-road running events and recommends clear reference to distance, surface, elevation change and altitude, type of event (continuous vs. staged), type of support, name and year of the event, governing body, and guidance on terminology. We further recommend to describe off-road running athletes by basic data, physiological determinants, training and competition characteristics in the scientific literature in order to facilitate and guide further research and practice.
Keywords: trail running; mountain running; ultramarathon; ultra running; athletes; classification